2016
DOI: 10.1016/j.apsusc.2016.06.178
|View full text |Cite
|
Sign up to set email alerts
|

The effects of copper doping on photocatalytic activity at (101) planes of anatase TiO2: A theoretical study

Abstract: Copper dopants are varyingly reported to enhance photocatalytic activity at titanium dioxide surfaces through uncertain mechanisms. In order to interpret how copper doping might alter the performance of titanium dioxide photocatalysts in aqueous media we applied density functional theory methods to simulate surface units of doped anatase (101) planes. By including van der Waals interactions, we consider the energetics of adsorbed water at anatase surfaces in pristine and copper doped systems.Simulation results… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 53 publications
(82 reference statements)
0
47
0
Order By: Relevance
“…They reported greater band gap reduction with increases in dopant concentration due to the covalent character of the Cu-O interaction leading to new states at the VBM. DFT studies have examined the impact of Cu-doping of the anatase (101) surface [62,63] with a focus on surface mediated phenomena in catalysis. A generalized gradient approximation (GGA) study showed that Cu dopants at the anatase (101) surface inhibit the dissociation of adsorbed water to hydroxyls [62].…”
Section: Density Functional Theory Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported greater band gap reduction with increases in dopant concentration due to the covalent character of the Cu-O interaction leading to new states at the VBM. DFT studies have examined the impact of Cu-doping of the anatase (101) surface [62,63] with a focus on surface mediated phenomena in catalysis. A generalized gradient approximation (GGA) study showed that Cu dopants at the anatase (101) surface inhibit the dissociation of adsorbed water to hydroxyls [62].…”
Section: Density Functional Theory Simulationsmentioning
confidence: 99%
“…DFT studies have examined the impact of Cu-doping of the anatase (101) surface [62,63] with a focus on surface mediated phenomena in catalysis. A generalized gradient approximation (GGA) study showed that Cu dopants at the anatase (101) surface inhibit the dissociation of adsorbed water to hydroxyls [62]. The authors attributed enhancements in the photocatalytic activity to arise instead from the electronic properties and inter-bandgap states, rather than the promotion of water dissociation.…”
Section: Density Functional Theory Simulationsmentioning
confidence: 99%
“…Therefore, to reach this high level of photoelectron efficiency, another transition metal, Cu, is used as a dopant 43 . Cu enhances the solar cell efficiency 44 and provides special resistance against wet, humid, and saline environments 45 . Cu also reduces the recombination rate of ZnO and enhances the electron injection efficiency rate from the dye to the conduction band of ZnO 46 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the electron-hole pair generated by photoexcitation of TiO 2 possesses a strong redox ability as a result of the wide band gap (E g = 3.0-3.2 eV), it does not effectively absorb visible light [4]. According to numerous experiments and theoretical calculations (Liu T. et al, December 2019, China United Test & Evaluation Qingdao CN110568122-A), the doping or heterojunction modification of TiO 2 not only effectively broadens its light absorption range but also substantially reduces the probability of photogenerated electron-hole pair recombination [5][6][7][8][9][10][11][12][13][14]. However, due to the complexity of the photocatalytic water-splitting reaction system, considerable controversy still exists regarding its reaction mechanism, reaction process, and kinetic behavior.…”
Section: Introductionmentioning
confidence: 99%